Mapping of Coastal Vulnerability Index on Coastal erosions in The Perspective of Economy (Study Area: Kecamatan Muara Gembong, Kabupaten Bekasi) - Aldila Pradhana; Wiwin Windupranata; Wisayantono Wisayantono (Indonesian Journal of Geospatial, 2014)
Abstract. Muara Gembong is a district that located in north coast of West Java and affected by the phenomena of coastal erosion. This phenomenon causes decreased land in Muara Gembong. To find out how vulnerable the villages in these districts by coastal erosion, it is necessary to map coastal vulnerability index. Value of coastal vulnerability index was obtained by classifying of coastal vulnerability index variable based on the value of the class and then it multiplied by the value of the weight of each variable. These variables defined into two, physical variables and non-physical variables (economy). The results of calculation are presented in tables and maps of coastal vulnerability index. Based on the research result, all coastal villages in Muara Gembong are in vulnerable conditions when calculated by non physical variables. If based on physical variables and combination variable of physical and nonphysical, three of five coastal villages are in vulnerable condition. Result of this research described the big potential of lose in economy sector. Keywords: Position, coordinates, Geodetic Reference System, Datum coordinates.